Health Information Seeking, Source Trust, and Culture: A Comparative Analysis of Health Information Trends and Needs Between Guam and the United States. Issue 4 (2nd April 2016) - Somera, Lilnabeth P.; Lee, Hye-Ryeon; Badowski, Grazyna; Cassel, Kevin
Abstract : The Guam population offers a unique glimpse into Americans of Pacific Island ancestry and their communication and information-seeking behaviors, experiences, and needs relevant to cancer. National surveys do not typically include the U.S. territories, so there are limited data on the health and cancer information–seeking behaviors of these populations, in which health disparities persist. To fill this information gap, we conducted a survey on health communication in Guam using a modified version of the Health Information National Trends Survey instrument supplemented with items measuring specific cultural factors and communication practices. The results of the survey ( N  = 511) revealed some differences in health and cancer information–seeking patterns in Guam and the mainland United States. Sociodemographic variables, including sex, age, education, income, and employment, were significantly associated with health and cancer information seeking and Internet use. Levels of trust in various information sources were differentiated in the Guam and mainland U.S. samples. Logistic regression models revealed differences in factors predicting health and cancer information seeking and Internet use. The results suggest that these health information–seeking patterns and factors should be taken into account when developing communication strategies for more effective prevention and control programs.